2016
DOI: 10.1134/s1063782616050110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium-selenide quantum dots on the conductivity and photoconductivity of nanocrystalline indium oxide

Abstract: The effect of cadmium-selenide quantum dots addition on the electrical and photoelectric properties of nanocrystalline indium oxide with nanocrystal dimensions in the range from 7 to 40 nm is studied. By impedance spectroscopy, it is shown that the addition of quantum dots substantially influences the resistance of interfaces between In 2 O 3 crystals. A change in the character of the photoconductivity spectrum of In 2 O 3 upon the addition of CdSe quantum dots is detected, and it is established that this chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Our recent investigations [35] of the effect of CdSe QDs on the electrical properties of nanocrystalline In 2 O 3 by impedance spectroscopy demonstrated that the addition of QDs substantially influences the resistance of interfaces between In 2 O 3 crystals. However, the behavior of the frequency dependence of the samples conductivity is defined only by the nanocrystalline structure of semiconductor matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent investigations [35] of the effect of CdSe QDs on the electrical properties of nanocrystalline In 2 O 3 by impedance spectroscopy demonstrated that the addition of QDs substantially influences the resistance of interfaces between In 2 O 3 crystals. However, the behavior of the frequency dependence of the samples conductivity is defined only by the nanocrystalline structure of semiconductor matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The use of CdSe [ 160 , 161 , 162 , 163 , 164 , 165 ] and PbS [ 166 ] quantum dots for the creation of photo- and gas sensitive nanocomposites is described in the literature. The sensor and photoelectric properties of nanocomposites based on semiconductor metal oxides ZnO, SnO 2 , In 2 O 3 , and CdSe colloidal QDswere studied in [ 161 , 162 , 163 , 164 ]. For sensitization, spherical CdSe quantum dots with an average diameter of 2.7 nm, stabilized with oleic acid, were used.…”
Section: Activation Of Gas Sensitivity Of Semiconductor Metal Oxides Under Visible Lightmentioning
confidence: 99%